Faktor tekanan dan kelembapan udara terhadap cuaca ekstrem di Surabaya pada Oktober 2023: Studi kasus Global Warming - Putri, Mareta Helmalia (Maliki Interdisciplinary Journal, 2024)
As the provincial capital, Surabaya is one of the government centers and a large city with a variety of complete public facilities. In this way, the density in the city will definitely have an impact on the environment. Such as vehicle fumes, industry and other factors that cause environmental imbalance. It can also allow extreme weather to occur which can cause more intense storms, hurricanes, floods, dry seasons, and many other weather phenomena that will have an impact on human economic and social life. The data obtained shows that pollution can affect the temperature of an area, with high temperatures the air pressure will be high and the humidity will be low, so the potential for rain is very minimal. That's why hot weather and temperatures will continue even into the evening. This will not happen if the pollution factor only occurs in a short time span.